Otherness, love and faith in Miguel de Unamuno’s philosophy of religion - von Zuben, Newton Aquiles (2021)
This article presents a study on the relation between religious feeling and the search for meaning for existence, based on Miguel de Unamuno’s philosophy of religion. This study seeks to explain how religious feeling, in the form of a personal faith, creates meaning for existence. For this, a study about alterity, love and faith and their articulation by the notion of personal conscience, in Unamuno’s philosophical anthropology. The search for meaning and the religious feelings are identified in the desire to not die. They are rooted in human affectivity, which contradicts logical and scientific reason. In the contradiction between faith and reason, it is up to faith, through the poetical word, to creat meaning for existence.